IMPLEMENTASI PENGAMBILAN JURUSAN SISWA MADRASAH ALIYAH SWASTA DI TANJUNGBALAI DENGAN METODE SAW - Melati, Putri; Siregar, Iqbal Kamil; Rahayu, Elly (STMIK Royal Kisaran, 2023)
Abstract: The school management routinely determines the majors of private students at Madrasah Aliya (MAS) every year. YMPI Private Madrasah Ariyah (MAS) is one of the MAs that implements the 2013 curriculum. One of the work programs in the MAS Curriculum is to register for the first year majors which will continue to the second year. In this case, a decision support system (DSS) is a computer interactive system that assists school management in making decisions. In this study the system development method used is the Prototyping Method. Prototyping is a system development method that is widely used. With this method, developers and customers can interact with each other during the system creation process. The system prototype method involves the user directly with analysis and design, very effective for system correction. A decision support system with the SAW (Simple Additive Weighting) method is used to solve the problem of choosing a major. The application of the SAW method is expected to support the decision-making process to choose a major that is in accordance with the students' academic grades while still in junior high schools beforehand as well as the IQ abilities of each student and the results of their interest in the chosen major. The research resulted in an application that is able to determine the choice of majors with the results of an application by determining the value/weight using the SAW method so that it can be determined that Abdul Rozak entered the Science major and Abil Akbar entered the Social Sciences major. Keywords: decision making system; selection of majors; SAW; criteria. Abstrak: Pihak manajemen sekolah rutin menentukan jurusan siswa swasta di Madrasah Aliya (MAS) setiap tahun. Madrasah Ariyah Swasta YMPI (MAS) merupakan salah satu MA yang menerapkan kurikulum 2013. Salah satu program kerja dalam Kurikulum MAS adalah mendaftar ke jurusan tahun pertama yang akan melanjutkan ke tahun kedua. Dalam hal ini, sistem pendukung keputusan (DSS) adalah sistem interaktif komputer yang membantu pihak manajemen sekolah dalam mengambil keputusan. Dalam penelitian ini metode pengembangan sistem yang digunakan adalah Metode kuantitatif. Dengan mengumpulkan data berupa angka dengan kriteria yang telah ditentukan mulai dari data nilai akademik IPA dan IPS, Nilai tingkat kecerdasan (IQ) serta nilai minat dari setiap siswa yang diperoleh dari kuisoner.Sistem pendukung keputusan dengan metode SAW (Simple Additive Weighting) digunakan untuk menyelesaikan masalah pemilihan jurusan. Penerapan metode SAW diharapkan dapat mendukung proses pengambilan keputusan untuk memilih jurusan yang sesuai dengan nilai akademik siswa saat masih di sekolah SLTP sebelmumnya serta kemampuan IQ masing-masing siswa serta hasil minat mereka ke jurusan pilihan tersebut. Penelitian menghasilkan aplikasi yang mampu menentukan pilihan jurusan dengan hasil sebuah aplikasi dengan menentukan nilai/bobot dengan menggunakan metode SAW sehingga dapat ditentukan bahwa Abdul Rozak masuk ke jurusan IPA serta Abil Akbar masuk kejurusan IPS. Kata kunci: sistem penentuan keputusan; pemilihan jurusan; SAW; kriteria